2021
DOI: 10.1155/2021/5540139
|View full text |Cite
|
Sign up to set email alerts
|

Fraxetin Inhibits the Proliferation and Metastasis of Glioma Cells by Inactivating JAK2/STAT3 Signaling

Abstract: Glioma is the most common brain tumor and is characterized by high mortality rates, high recurrence rates, and short survival time. Migration and invasion are the basic features of gliomas. Thus, inhibition of migration and invasion may be beneficial for the treatment of patients with glioma. Due to its antitumor activity and chemical reactivity, fraxetin has attracted extensive interest and has been proven to be an effective antitumor agent in various cancer types. However, currently, the potential effects of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…And these inflammatory factors act on the liver cell biofilms and damage the liver cells, thereby causing liver failure [ 21 , 22 ]. Meanwhile, according to the study, interleukins IL-10 and IL-6 can upregulate CD163 expression in monocytes [ 23 , 24 ]. Unlike cytokines, most proinflammatory factors such as IFN γ , LPS, and TNF- α can downregulate the expression of CD163 [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…And these inflammatory factors act on the liver cell biofilms and damage the liver cells, thereby causing liver failure [ 21 , 22 ]. Meanwhile, according to the study, interleukins IL-10 and IL-6 can upregulate CD163 expression in monocytes [ 23 , 24 ]. Unlike cytokines, most proinflammatory factors such as IFN γ , LPS, and TNF- α can downregulate the expression of CD163 [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fraxetin also inhibits MCF-7 breast cancer cells proliferation of and induces cell apoptosis [ 3 ]. A recent study reported that Fraxetin inhibits proliferation and metastasis of glioma cells by inactivating JAK2/STAT3 signaling [ 6 ]. Tumor invasion and metastasis remain the major causes of deaths in prostate cancer patients [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Afterward, a crystal pipette tip was employed to create a linear gap between the cells. The cells were washed with phosphate buffer solution (PBS) three times before the addition of new serum-free medium containing a series concentration of Fraxetin (0, 10, 20, and 40 μM) for another 48 h [ 6 ]. Finally, images of the culture area were captured under a light microscope (magnification, x100; Olympus Corporation).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Yangyang Guo et al reported that FXT inhibited the development of pancreatic cancer by antagonizing STAT3 activation (Guo et al, 2021). Of note, Liangchen Qu et al found that FXT inhibits the proliferation and metastasis of glioma cells by inhibiting the JAK2/STAT3 signaling pathway (Qu et al, 2021). In addition, Ying Su et al found that JAK2 inhibitors and si‐STAT3 inhibited the level of miR‐21 in human renal cell carcinoma cells (Su et al, 2017), suggesting that FXT may inhibit the expression of miR‐21‐3p by inhibiting the JAK2/STAT3 signaling pathway.…”
Section: Discussionmentioning
confidence: 99%